The changes of functional, structural and hemodynamic parameters of the optic disc in patients with primary open-angle glaucoma and diabetes mellitus in long-term follow-up - A. Zh. Fursova; Ju. A. Gamza; O. G. Gusarevich; A. S. Derbeneva; M. A. Vasil’eva (Российский офтальмологический журнал, 2021)
Purpose: to study the long-term changes of functional, structural, and hemodynamic parameters of the optic nerve in primary open-angle glaucoma (POAG) accompanied by diabetes mellitus (DM).Material and methods. The study involved 258 patients (258 eyes), which were divided into five groups: 1st group — 58 patients with stage I POAG and DM; 2nd group — 50 patients (50 eyes) with stage I POAG; 3rd — 50 patients with stage III POAG and DM; 4th — 50 patients with stage III POAG; 5th — 50 patients with DM. In addition to a complete ophthalmological examination, the patients underwent spectral optical coherence tomography (OCT), OCT angiography of the optic nerve head and macula. The observation period was 24 months.Results. The worst decrease in maximally corrected visual acuity was noted in patients with DM + POAG (groups 1 and 3): in 1 year of observation — stage I — 10.29%, stage III — 7.32 %, in control groups with isolated POAG stages I and III, 1.15 and 2.04%, respectively, in patients with DM, 1.39%; in 2nd year — 14.71 and 14.63% with a comorbid course of the disease and 1.15 and 4.08% in the absence of DM, respectively. The MD index in the group DM + POAG stage I after 12 months was significantly lower compared to patients with stage I POAG (by 5.05%), after 24 months by 12.12, 0.34 and 1.69%, respectively (p £ 0.05). The groups of comorbid patients showed lower average thickness levels of the retinal nerve fibers layer than in the control groups: 78.81 ± 11.39 μm at stage I and 63.08 ± 10.32 μm at stage III. A similar pattern was noted for the thickness of the neuroretinal rim and its areas as well indicators of the optic disc excavation (volume and c/d ratio).No significant difference was noted in the density of the optic nerve disc perfusion in stages I and III POAG with DM against the respective control groups during the first visit, but we noted a significantly lower vascular density in patients with the initial stage of POAG and DM (0.39 ± 0.04 / mm) than in patients with isolated glaucoma (0.42 ± 0.03 / mm). As the disease progressed, there was a further significant decrease in the average indicators of optic nerve disc perfusion and vascular density (group 3: 39.17 ± 3.43% and 0.33 ± 0.03 / mm).Conclusion. The study of the changes of visual, functional, structural and hemodynamic parameters of the optic nerve showed a faster rate of progression of glaucomatous optic neuropathy if accompanied with DM.